PkM PENGENALAN DAN PENGEMBANGAN POTENSI RUMPUT LAUT DI PULAU RAAM SEBAGAI ALTERNATIF MATA PENCAHARIAN NELAYAN - Ahmad Fahrizal; Intan N. B. Hismayasari; Ernawati Ernawati; Ratna Ratna (Buletin SWIMP, 2021)
Raam Island is one of 3 islands in the Sorong Islands District. The enormous potential for marine cultivation supported by adequate land becomes an alternative job opportunity for the people on the island. The introduction of the potential and methods of seaweed cultivation needs to be introduced to the community as a first step to add insight and improve the capabilities of coastal communities with the aim of providing alternative knowledge and potential employment opportunities to generate income that supports the main livelihood activities of fishermen. Activities are carried out through offline learning to the community, especially fishermen and fisherwomen. The target partners who were trained were limited because PPKM consisted of 10 participants who came from the Raam island community. The results of monitoring target partners can recognize material in the form of potential and methods of seaweed cultivation